2018
DOI: 10.2174/1871520617666171114094847
|View full text |Cite
|
Sign up to set email alerts
|

Halilectin-3, a Lectin from the Marine Sponge Haliclona caerulea, Induces Apoptosis and Autophagy in Human Breast Cancer MCF7 Cells Through Caspase-9 Pathway and LC3-II Protein Expression

Abstract: The apoptotic effect of H3 may be related to a balance between apoptotic and autophagic cell death, mediated by increased expression of CASP 9 and LC3-II. To the best of our knowledge this is the first report about a sponge lectin triggering both apoptosis and autophagy in MCF7 cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…LC3-II of 14 kD is located on the autophagosome membrane, and its content is proportional to the number of auto-phagosome vesicles, so LC3-II is one of the marker proteins of auto-phagosome formation [8]. LC3-II/LC3-I ratio is usually adopted to reflect the number of auto-phagosomes and the level of autophagy in cells [9]. Studies have found that PI3K I/Akt/ mTOR and PI3K III/Beclin-1/Bcl-2 are important signaling pathways involved in cell autophagy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…LC3-II of 14 kD is located on the autophagosome membrane, and its content is proportional to the number of auto-phagosome vesicles, so LC3-II is one of the marker proteins of auto-phagosome formation [8]. LC3-II/LC3-I ratio is usually adopted to reflect the number of auto-phagosomes and the level of autophagy in cells [9]. Studies have found that PI3K I/Akt/ mTOR and PI3K III/Beclin-1/Bcl-2 are important signaling pathways involved in cell autophagy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of caspase-3, caspase-9 and Bax/Bcl-2 indicate that cells are in a state of induced apoptosis. 25,26 It is reported that caspase-3 and Bax can respond to ganoderma lucidum spore oil in vitro and in vivo treatment of BC. The inactivated caspase-9 is related to the tumor survival of triple-negative BC, and Bcl-2 is a vital factor in the antiapoptosis defense mechanism of BC.…”
Section: Dovepressmentioning
confidence: 99%
“…In particular, H3 upregulated the microtubule-associated protein 1A/1B-light chain 3 (LC3) expression, promoting the accumulation of LC3-II (Table 2). Contextually, autophagosome vesicles have been identified microscopically [66]. The authors of the study [40] hypothesize that both apoptosis and autophagy can be triggered thanks to Bcl-2 downregulation or p53 upregulation.…”
Section: Phylum Poriferamentioning
confidence: 99%
“…The authors of the study [40] hypothesize that both apoptosis and autophagy can be triggered thanks to Bcl-2 downregulation or p53 upregulation. To complete the picture, H3 has been found able to promote anoikis, a particular form of cell death that happens when cells are stimulated to detach from the extracellular matrix [66]. In normal conditions, cells need to adhere to the tissue where they grow since the essential growth factors and other survival signals are provided by the extracellular matrix and proximal cells [88].…”
Section: Phylum Poriferamentioning
confidence: 99%
See 1 more Smart Citation